Plant Coumestans: Recent Advances and Future Perspectives in Cancer Therapy - Nehybova, Tereza; Smarda, Jan; Benes, Petr (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Natural products are often used in drug development due to their ability to form unique and diverse chemical structures. Coumestans are polycyclic aromatic plant secondary metabolites containing a coumestan moiety, which consists of a benzoxole fused to a chromen-2-one to form 1-Benzoxolo[3,2-c]chromen-6-one. These natural compounds are known for large number of biological activities. Many of their biological effects can be attributed to their action as phytoestrogens and polyphenols. In the last decade, anticancer effects of these compounds have been described in vitro but there is only limited number of studies based on models in vivo. More information concerning their in vivo bioavailability, stability, metabolism, toxicity, estrogenicity, cellular targets and drug interactions is therefore needed to proceed further to clinical studies. This review focuses on coumestans exhibiting anticancer properties and summarizes mechanisms of their toxicity to cancer cells. Moreover, the possible role of coumestans in cancer prevention is discussed.
Keywords: glycyrol